Predominant Nearshore Sediment Dispersal Patterns in Manila Bay - Siringan, Fernando; Ringor, Cherry (Science Diliman: A Journal of Pure and Applied Sciences; Vol 9, Nos 1 & 2 (1997), 2007)
Net nearshore sediment drift patterns in Manila Bay were determined by combining the coastal geomorphology depicted in 1 : 50,000scale topographic maps and Synthetic Aperture Radar (SAR) images, with changes in shoreline position and predominant longshore current directions derived from the interaction of locally generated waves and bay morphology. Manila Bay is fringed by a variety of coastal subenvironments that reflect changing balances of fluvial, wave, and tidal processes. Along the northern coast, a broad tidal-river delta plain stretching from Bataan to Bulacan indicates the importance of tides, where the lateral extent of tidal influences is amplified by the very gentle coastal gradients. In contrast, along the Cavite coast sandy strandplains, spits, and wave-dominated deltas attest to the geomorphic importance of waves that enter the bay from the South China Sea. The estimates of net sediment drift derived from geomorphological, shoreline-change, and meteorological information are generally in good agreement. Sediment drift directions are predominantly to the northeast along Cavite, to the northwest along Manila and Bulacan, and to the north along Bataan. Wave refraction and eddy formation at the tip of the Cavite Spit cause southwestward sediment drift along the coast from Zapote to Kawit. Geomorphology indicates that onshore-offshore sediment transport is probably more important than alongshore transport along the coast fronting the tidal delta plain of northern Manila Bay. Disagreements between the geomorphic-derived and predicted net sediment drift directions may be due to interactions of wave-generated longshore currents with wind- and tide-generated currents.